The effect of anxiety and depression on the health-related quality of life of severe acute pancreatitis survivors: structural equation modeling approach - Wang, Xueting; Zhan, Weili; Huang, Ling; Guo, Yunmei; Wang, Yousha; Tan, Huiwen; Wang, Lianhong (Frontiers in Psychiatry, 2023)
Background Understanding the relationship between anxiety, depression and health-related quality of life (HRQOL) provides important clues to alleviate anxiety, depression and improve HRQOL in patients after severe acute pancreatitis(SAP). The aim of this study was to examine the effects of anxiety and depression on HRQOL in post-SAP patients using structural equation modelling. Methods A cross-sectional study design was used and 134 patients with SAP from the Affiliated Hospital of Zunyi Medical University were recruited. Data collected included demographic and clinical characteristics, the English Standard Short Form 36 (SF-36) Health Survey, The Self-rating Anxiety Scale(SAS) and The Self-rating Depression Scale(SDS). Structural equation modelling analysis was conducted using the AMOS 24.0 program. Results The mean of HRQOL score was 49.42(SD=23.01). The prevalence of anxiety and depression in post-SAP patients was 33.6% and 34.3%, respectively. Both anxiety and depression have a direct negative impact on HRQOL(β= −0.360, p＜0.001; β= −0.202, p=0.034) . Anxiety also negatively affects HRQOL indirectly through depression (β= −0.118, p=0.043) . The analysis of the covariance structure revealed that the resulting model had a reasonable goodness of fit. Conclusion Anxiety and depression reduce the quality of life of SAP patients during recovery. Regular assessment and management of the anxiety and depression status of SAP patients is necessary and will help them improve their HRQOL more effectively.